Comparative analysis of fatty acid metabolism based on transcriptome sequencing of wild and cultivated Ophiocordyceps sinensis - Zhang, Han; Yue, Pan; Tong, Xinxin; Gao, Tinghui; Peng, Ting; Guo, Jinlin (PeerJ, 2021)
Background Ophiocordyceps sinensis is a species endemic to the alpine and high-altitude areas of the Qinghai-Tibet plateau. Although O. sinensis has been cultivated since the past few years, whether cultivated O. sinensis can completely replace wild O. sinensis remains to be determined. Methods To explore the differences of O. sinensis grown in varied environments, we conducted morphological and transcriptomic comparisons between wild and cultivated samples who with the same genetic background. Results The results of morphological anatomy showed that there were significant differences between wild and cultivated O. sinensis, which were caused by different growth environments. Then, a total of 9,360 transcripts were identified using Illumina paired-end sequencing. Differential expression analysis revealed that 73.89% differentially expressed genes (DEGs) were upregulated in O. sinensis grown under natural conditions compared with that grown under artificial conditions. Functional enrichment analysis showed that some key DEGs related to fatty acid metabolism, including acyl-CoA dehydrogenase, enoyl-CoA hydratase, 3-ketoacyl-CoA thiolase, and acetyl-CoA acetyltransferase, were upregulated in wild O. sinensis. Furthermore, gas chromatography-mass spectrometry results confirmed that the fatty acid content of wild O. sinensis was significantly higher than that of cultivated O. sinensis and that unsaturated fatty acids accounted for a larger proportion. Conclusion These results provide a theoretical insight to the molecular regulation mechanism that causes differences between wild and cultivated O. sinensis and improving artificial breeding.
Keywords: Ophiocordyceps sinensis; Wild-grown; Cultivated; Transcriptome; Fatty acid metabolism; GC-MS